PENGARUH BELANJA LANGSUNG DAN TIDAK LANGSUNG TERHADAP EKUITAS DANA (Studi Pada Kabupaten/Kota di Sulawesi Tengah) - Chazbullah, Muchammad Chusni (Katalogis, 2018)
AbstractThe goals of this study is to determine and analyze the growth of direct expenditure, indirect expenditure, and equity funds as well as to determine simultaneous and partial influence of direct and indirect expenditure on equity funds. Sample of the study consists of 11 districts/towns in Central Sulawesi that is selected with purposive sampling method. Method of analysis is descriptive and multiple linear regressions. The result find that the average growth of both direct and indirect expenditure is decreased while the average of equity funds has been increasing. The result of simultaneous test indicates that direct and indirect expenditures have significant influence on equity funds. Determinant coefficient of R-Square value of 0,770 that indicates the influence of direct and indirect expenditure on equity funds is 77,00%, while 23,00% influenced by variables that are mot studied.